Treatment Patterns and Radical Cystectomy Outcomes in Patients Diagnosed With Urothelial Nonmetastatic Muscle‐Invasive Bladder Cancer in the United States - Davies‐Teye, Bernard Bright; Siddiqui, M. Minhaj; Zhang, Xiao; Johnson, Abree; Burcu, Mehmet; Onukwugha, Eberechukwu; Hanna, Nader (Cancer medicine (Malden, MA), 2025)
ABSTRACT Purpose To characterize trends and patterns in treatment characteristics and perioperative outcomes of patients with urothelial muscle‐invasive bladder cancer (MIBC). Materials and Methods We utilized the National Cancer Database to assess trends and patterns in treatment modalities (radical cystectomy [RC] with or without neoadjuvant/adjuvant treatments, trimodal bladder‐sparing treatment [trimodal treatment], and others) among MIBC patients diagnosed between 2004 and 2017. We also assessed trends and patterns of short‐term post‐surgery outcomes, including 30‐day and 90‐day mortality, and readmissions. Results Among 83,259 MIBC patients, those who received RC, trimodal treatment, and transurethral resection of bladder tumor (TURBT) plus chemotherapy were 34,715 (41.7%), 7,372 (8.9%), and 6,171 (7.4%), respectively. A substantial proportion (29,314; 35.2%) of MIBC patients received other treatments, including TURBT‐only. From 2004 through 2017, the proportion of MIBC patients who utilized guideline‐recommended treatments, whether RC (from 36.4% to 42.8%) or trimodal treatment (from 7.9% to 10.2%), increased. Among those who received RC, there was a substantial increase in neoadjuvant chemotherapy (NAC) utilization, from 7.8% to 29.4%. Conversely, utilization of RC without perioperative treatments decreased from 62.3% to 32.7%. There was a significant decrease in 30‐day (2.8%–1.8%) and 90‐day (7.1%–5.3%) mortality rates among RC recipients. Conclusion There was a shift in treatment modalities for MIBC, with increased utilization of RC with NAC. A decrease in post‐surgery mortality rates may indicate improved outcomes, although the unmet need for NAC utilization requires further investigation. Precise This study characterized trends and patterns in treatment characteristics and perioperative outcomes of patients with urothelial muscle‐invasive bladder cancer (MIBC). We utilized the National Cancer Database to assess trends and patterns in treatment modalities (radical cystectomy [RC] with or without neoadjuvant/adjuvant treatments, trimodal bladder‐sparing treatment [trimodal treatment], and others) among MIBC patients diagnosed between 2004 and 2017. There was a shift in treatment modalities for MIBC, with increased utilization of RC with NAC. A decrease in post‐surgery mortality rates may indicate improved outcomes, although the unmet need for NAC utilization requires further investigation.